Chapter 我是中国人: Identity and social integration of Chinese youth in the Marche region - Perna, Meri (Studi e saggi, 2020)
This article analyzes the issues of identity and social integration of Chinese youth in the Marche region. The focus on these two themes arises from the recent increase in the number of Chinese students in schools in this region. This change points to a need to study an unexplored phenomenon. In this regard, the intention of this contribution is, on the one hand, to observe the dynamics related to social integration of these young people and to understand how they navigate their multiple identities, and, on the other hand, to provide guidance for future research as well as useful tools to create a welcoming and inclusive environment for them to live in. Following a review of the literature, this article analyzes research results regarding data collected from 198 young people and 21 teachers, and concludes with insights into the identity and social integration problems confronting Chinese youth in the region.